Surface sperm cell ubiquitination directly impaired blastocyst formation rate after intracytoplasmic sperm injection in pig - Petelak, Ales; Krylov, Vladimir (Theriogenology, 2019)
The effect of extracellular sperm ubiquitination was examined from many aspects and the majority of existing studies negatively correlated the amount of highly ubiquitinated sperm cells in the sample with the ejaculate quality and the fertilization success rate. In the present study, we compared an early embryonic development up to blastocyst stage in the pig using two defined sperm cell populations sorted by flow cytometry (FACS) based on the rate of the extracellular ubiquitination. This novel approach allows studying the direct effect of extracellular ubiquitin (eUb), which is a marker for epididymal recognition and degradation of defective sperm cells. We further examined the hypothesis that eUb could be recognized directly in the ooplasm. In the porcine model, the significance of results might be seriously affected by a high variability among sperm cell doses from individual boars as well as by the variability among separate sample collections. To overcome this obstacle, we used cryopreserved sperm cells from a single dose. Comparison of an early embryonic development employing intracytoplasmic sperm cell injection (ICSI) with cryopreserved (frozen/thawed, F/T) and fresh sperm cells did not reveal significant difference regarding blastocyst formation rate. We also observed no difference in the male and female pronuclei formation and the first zygote cleavage after fertilization of oocytes with high or non-ubiquitinated sperm cells sorted by FACS. However, results of the early embryonic development to the blastocyst stage showed the difference between both experimental groups (16.67% of blastocysts in non-ubiquitinated group vs. 6.20% of blastocyst in the high-ubiquitinated group, P < 0.001). We further confirmed the negative effect of eUb by the masking of Ub epitopes with the appropriate primary antibody in fresh sperm cells prior to ICSI. This procedure improved the blastocyst formation rate from 14.19% in the untreated group to 24.03% concerning antibody masked sperms (P < 0.01). We conclude our results support a generally accepted hypothesis concerning the negative correlation of the presence of eUb on the sperm cell membrane and developmental competence of fertilized oocytes. However, experiments with masking Ub antibody indicate the direct negative effect of the membrane ubiquitin rather than sperm cell quality on the early embryonic development to the blastocyst stage, at least in the porcine model.
Keywords: Animals; Cryopreservation; Sperm Injections, Intracytoplasmic; intracytoplazmatické injekce spermie; Female; Embryo Culture Techniques; ubikvitinace; spermie; průtoková cytometrie; ženské pohlaví; Spermatozoa; blastocysta; Oocytes; Semen Preservation; Flow Cytometry; oocyty; prasata; kryoprezervace; Blastocyst; Male; Swine; Ubiquitination; zvířata; mužské pohlaví; kultivace embrya; uchování spermatu